Long Term Economic Development Demand, Finance, Organization, Policy and Innovation in a Schumpeterian Perspective - Pyka, Andreas.; Andersen, Esben Sloth. (Economic Complexity and Evolution, 2013)
The book gives an overview of important research topics recently addressed in evolutionary Neo-Schumpeterian Economics. The list of research questions and applications of Neo-Schumpeterian reasoning impressively demonstrates the rich possibilities ranging from theoretical issues addressing human behaviour to applied areas like the emergence of biotechnology in developing countries, the role of innovation on financial markets and the R&D strategies of multinational enterprises. The chapters in this book bring together a rich set of new analytical and empirical methodologies which allow for new relevant and rigorous insights in innovation processes which are responsible for economic development and structural change.